The Effect of Banana Frond Waste Fibers Compared to Glass Fibers on The Mechanical Properties of Composites - Azizi, Muhammad; Susilo, R. Dwi Pudji; Ariansyah, Nando; Fitri, Muhamad (JMPM (Jurnal Material dan Proses Manufaktur), 2025)
This study investigates the mechanical properties of composites reinforced with banana frond waste fibers compared to those reinforced with traditional glass fibers. The increasing environmental concerns and the need for sustainable materials have driven the exploration of natural fibers as viable alternatives to synthetic fibers in composite materials. Banana frond waste, a byproduct of banana cultivation, offers a renewable and biodegradable option for composite reinforcement.Composites were fabricated using both banana frond waste fibers and glass fibers, and their mechanical properties, including tensile strength, bending strength, and impact resistance, were evaluated and compared. The results indicated that while glass fiber composites exhibited higher overall mechanical performance, banana frond waste fiber composites showed competitive properties, particularly in terms of impact resistance and specific strength. The natural fibers demonstrated adequate bonding with the polymer matrix, contributing to the composite's overall integrity.Moreover, the use of banana frond waste fibers significantly reduced the composite's environmental footprint, making them a promising alternative for various applications where moderate mechanical performance is sufficient. The study highlights the potential of banana frond waste fibers as a sustainable reinforcement material, encouraging further research and development in this area to optimize their mechanical properties and broaden their application scope.